2021
DOI: 10.3389/fmolb.2021.758337
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer, Papillomavirus, and miRNA Dysfunction

Abstract: Cervical cancer is the leading cause of death by cancer in women from developing countries. Persistent infection with high-risk human papillomavirus (HPV) types 16 and 18 is a major risk factor for cervical carcinogenesis. Nevertheless, only a few women with morphologic expression of HPV infection progress into invasive disease suggesting the involvement of other factors in cervical carcinogenesis. MicroRNAs (miRNAs) are conserved small non-coding RNAs that negatively regulate gene expression including genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 108 publications
0
27
0
13
Order By: Relevance
“…In 2020, the World Health Organization (WHO) reported 604,127 new cases of cervical cancer (CESC) and 341,831 CESC-related casualties ( 1 ). Seventy percent of patients of the CESC and CESC-related deaths were Human papillomavirus (HPV) type 16 and 18 positive ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, the World Health Organization (WHO) reported 604,127 new cases of cervical cancer (CESC) and 341,831 CESC-related casualties ( 1 ). Seventy percent of patients of the CESC and CESC-related deaths were Human papillomavirus (HPV) type 16 and 18 positive ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seventy percent of patients of the CESC and CESC-related deaths were Human papillomavirus (HPV) type 16 and 18 positive ( 2 ). The HPV, a non-enveloped double-stranded DNA virus, is a well-studied transmitter of sexual infections worldwide ( 1 ). Many HPV infections have no symptoms, and 90% resolve spontaneously within two years ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In cervical carcinoma, miRNAs promote tumor proliferation, migration, invasion, and influence apoptosis and chemoresistance. Examples are miR21, which influences Akt/mTOR pathway, proliferation, growth, and EMT [ 140 ]; miR375, which targets E-cadherin; and miR138, which targets EZH2, influencing chromatin remodeling [ 141 , 218 ]. It was observed that viral proteins E6 and E7 increase the expression of miR18a [ 137 ], influencing Hippo signaling, in human papilloma virus (HPV)-associated cervical carcinoma.…”
Section: Mirna In Malignant Tumorsmentioning
confidence: 99%
“…Human papillomaviruses (HPVs) are classified into two groups: low risk (LR-HPVs) and high risk (HR-HPVs) depending on their association with precursor lesions and their malignant potential, and among HR-HPVs, the most important types are HR-HPV HPV16 and HPV18 [ 218 ].…”
Section: Mirna In Viral Diseasesmentioning
confidence: 99%
“…Human papillomaviruses (HPV) play a key role in causing 85% of cervical death in developing countries. They are responsible for 604,127 new cases with 341,831 deaths worldwide in 2020 (Sherris et al, 2001;Bañuelos-Villegas et al, 2021). Among them, HPV 52 is the top three oncogenic HPV, which is considered one of the threatening types that spread throughout the Indonesian female population (http://www.hpvcentre.net/).…”
Section: Introductionmentioning
confidence: 99%